FUNGAL REMAINS FROM THE LATE RIPHEAN - Hermann T.N.; Podkovyrov V.N. (My University, 2006)
The paper describes organic remains of one billion years old from the Lakhanda microbiota of the Uchur-Maya Region of southeastern Siberia. The microfossils were discovered on organic sapropelic films. The preserved morphological characters and some developmental stages of the ancient organisms, which are fixed in fossil state, suggest that some of them resembled zygomycetes. Other microfossils under consideration are comparable to reproductive structures of myxomycetes in the type of fusion of spheroid cells and formation of various types of aggregation (sori). Colonies of unicellular microfossils that are arranged in a branching pseudomycelium superficially resemble yeasts. The presence in the same biota of fungal remains belonging to the Myxomycota and Mycota, as well as members of xanthophyte vaucherian algae, indicates that various branches of eukaryotes might have developed in parallel even earlier than the Late Riphean. © Pleiades Publishing, Inc. 2006.
Keywords: FUNGI; LAKHANDA MICROBIOTA; LATE RIPHEAN; MICROFOSSILS; MYXOMYCETES; REPRODUCTIVE STRUCTURES; SIBERIA; YEAST FUNGI; ZYGOMYCETES; Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей